Effect of Sensory Relearning on Sensory and Motor Functions of the Hand in Patients with Carpal Tunnel Syndrome: A Randomized Controlled Clinical Trial - M. Elbalawy, Youssef; M. Fahmy, Ebtesam; I. Taha, Shreen; El- Hamied I. El Sherbini, Abdel; I. Abdelghany, Abdelrhman; R. El-Serougy, Hager (International Journal of Psychosocial Rehabilitation, 2020)
Background: Carpal tunnel syndrome (CTS) is the most common type of entrapment neuropathy caused by compression of the median nerve as it passes through the carpal tunnel. Aim: To investigate the effect of somatosensory relearning on sensory and motor functions of the hand in patients with carpal tunnel syndrome. Subjects and Methods: Thirty-two female patients with CTS, aged 20-50 years, participated in the study. They were randomly assigned to two equal groups: Group I (experimental group) received sensory relearning in addition to a standard physical therapy program, and Group II (control group) received a standard physical therapy program consisting of traditional therapeutic exercises only. Assessment was done pre- and post-treatment using the Semmes-Weinstein monofilament (SWM) test to measure the sensory threshold and a handheld dynamometer to measure grip strength of the affected hand. Results: There was a statistically significant increase in sensory threshold of the affected hand in group (I) post-treatment. In addition, there was a statistically significant increase in grip strength of the affected hand in both groups post-treatment. Comparison between groups revealed a significant difference in the measured parameters post-treatment in favor of group I. Conclusion: Sensory relearning is effective in improving sensory threshold and grip strength of the affected hand when added to the standard physical therapy program in patients with CTS.